The trypanosomiases - Maudlin, I.; Holmes, P. H.; Holmes, P. H.; Maudlin, I.; Miles, M. A.; Miles, M. A. (Wallingford :CABI Publishing, 2004)
This reference book includes comprehensive coverage of the biology and control of African, Asian and South American trypanosomiasis in man and animals. It describes recent research developments in the biology and molecular biology of trypanosomes and their vectors, and methods in diagnosis and control, such as tsetse trapping. Different sections of the book are devoted to biology of trypanosomes (part 1), vector biology (part 2), epidemiology and diagnosis (part 3), pathogenesis (part 4), disease impact (part 5), chemotherapy and disease control (part 6), and vector control (part 7). This book is intended for researchers in the areas of parasitology, medical and veterinary science, and biology, and for public health and veterinary staff and international agencies concerned with reducing mortality and morbidity due to trypanosomiasis.
Keywords: HH000 - Pathogen, Pest, Parasite and Weed Management (General); HH405 - Pesticides and Drugs; Control, (New March 2000); LL822 - Protozoan, Helminth, Mollusc and Arthropod Parasites of Animals, (New March 2000); LL823 - Veterinary Pests, Vectors and Intermediate Hosts, (New March 2000); LL886 - Diagnosis of Animal Diseases, (New March 2000); VV220 - Protozoan, Helminth and Arthropod Parasites of Humans, (New March 2000); VV230 - Public Health Pests, Vectors and Intermediate Hosts, (New March 2000); VV720 - Diagnosis of Human Disease, (New March 2000); YY000 - Zoology of Wild Animals (Vertebrates and Invertebrates) (General), (New March 2000); YY300 - Genetics and Molecular Genetics (Wild Animals), (New March 2000); ZZ360 - Molecular Biology and Molecular Genetics, (Discontinued March 2000, Reinstated and Revised June 2002); ZZ390 - Microbiology (General); ZZ395 - Genetics and Molecular Biology of Microorganisms, (New March 2000); ZZ900 - Techniques and Methodology